2020
DOI: 10.1128/msystems.00640-20
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the Virome in Lab- and Field-Collected Aedes albopictus Mosquitoes across Different Developmental Stages and Possible Core Viruses in the Publicly Available Virome Data of Aedes Mosquitoes

Abstract: Our study revealed that the virome was very stable across all developmental stages of both lab-derived and field-collected Aedes albopictus. The data representing the core virome in lab A. albopictus proved the vertical transmission route of these viruses, forming a “vertically transmitted core virome.” Field mosquitoes also contained this stable vertically transmitted core virome as well as additional viruses, which probably represented “environment-derived core virome” and which therefore were less stable ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
97
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(107 citation statements)
references
References 59 publications
10
97
0
Order By: Relevance
“…Previous studies have shown that the viromes of the two important mosquitoes, A. aegypti and C. quinquefasciatus, have their own relatively stable core virome, which might have important implications for the competence to host the relevant arboviruses 17 . Moreover, further investigation revealed that the core virome was very stable across all developmental stages of both lab-derived and field-collected A. albopictus 35 . Our results suggested that different cryptic species of B. tabaci clearly harbor specific core virus/viruses (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that the viromes of the two important mosquitoes, A. aegypti and C. quinquefasciatus, have their own relatively stable core virome, which might have important implications for the competence to host the relevant arboviruses 17 . Moreover, further investigation revealed that the core virome was very stable across all developmental stages of both lab-derived and field-collected A. albopictus 35 . Our results suggested that different cryptic species of B. tabaci clearly harbor specific core virus/viruses (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…3b), indicating a long-term coevolution between these ISVs and cryptic species of whitefly. Because the majority of the whitefly datasets used in this study are from public databases and are mostly derived from lab cultures, it is expected that the cryptic-species-specific core viruses in these whitefly cultures might constitute a vertically transmitted core virome, whereas the field whitefly dataset (FY-Q) likely harbors distinct environmentally-derived viruses (BtNeLV1-3, BtBeLV1-6, and BtBromoLV1-6) as described previously 35 . Nevertheless, more investigation is needed to confirm this hypothesis due to limited whitefly datasets from the field used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, which have primarily focused on analysis of viruses, have expanded our understanding of the breadth of viral diversity present in mosquito populations worldwide. More recently, similar approaches have been applied to examine the mosquito virome across different life stages of both lab-reared and wild-caught Aedes albopictus mosquitoes, providing intriguing insights to the potential stability and diversity of the mosquito virome ( Shi et al, 2020 ). Despite these insights, key epidemiologic information needed to direct interventions is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…vpiRNAs can be determined by a ping-pong signature (U 1 -A 10 ) and 10 nt complementary overlapping reads. For the San Gabriel virus and all segments of Aedes phasma virus [ 58 , 146 ], as well as individual segments of TMTLV and WSBLV-4, we observed a ping-pong signature (U 1 -A 10 ) and over-represented complementary 10 nt overlapping pairs of sRNA from reads of 24–29 nt from these viruses ( Supplementary File S2 ). The absence of a predominant 21 nt species of vsiRNA targeting CppDNV and WSBLV-4 in Ae.…”
Section: Resultsmentioning
confidence: 99%